2013
DOI: 10.3349/ymj.2013.54.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Mask Airway Insertion in Adults: Comparison between Fully Deflated and Partially Inflated Technique

Abstract: PurposeThe laryngeal mask airway (LMA) is a supraglottic airway device designed to seal around the laryngeal inlet. A controlled study was designed to compare the effectiveness and complications in inserting the LMA when the cuff is fully deflated and partially inflated.Materials and MethodsAmerican Society of Anesthesiologists physical status I or II 172 female patients scheduled for gynecologic procedures were included in this study. Patients were randomly allocated into one of the two groups; fully deflated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
2
13
0
1
Order By: Relevance
“…Each participant in our study received the LMA-Classic with size adjusted by weight and the cuff fully deflated. This treatment is in accordance with earlier research from Jiwon An, et al [6] comparing fully and partially deflated LMA, resulting in a more accurate method if the cuff was fully deflated [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Each participant in our study received the LMA-Classic with size adjusted by weight and the cuff fully deflated. This treatment is in accordance with earlier research from Jiwon An, et al [6] comparing fully and partially deflated LMA, resulting in a more accurate method if the cuff was fully deflated [7].…”
Section: Discussionsupporting
confidence: 91%
“…Choo, et al [7] compared the position of the LMA-Flexible in 108 patients undergoing dental surgery using either a…”
Section: Discussionmentioning
confidence: 99%
“…Despite the manufacturers recommendation many anaesthetists inserted the LMA with a partially inflated cuff. Having said this, earlier studies have not confirmed that the insertion technique is associated with POST [29,30]. The anatomy of the pharynx differs between the sexes [31] and it is possible that currently used LMAs are devised to better suit the anatomical features of the male pharynx rather than the female and therefore the lower incidence of POST in men.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Laryngeal mask airway jenis klasik mempunyai kemampuan menjaga jalan napas secara adekuat serta menyebabkan angka kejadian komplikasi dan morbiditas faringolaringeal yang rendah. 5 Suatu penelitian merekomendasikan cara pemasangan LMA jenis klasik dengan teknik standar. 6 Teknik standar pemasangan LMA jenis klasik adalah dengan cara mengempiskan balon LMA, menekan ujung LMA ke permukaan palatum durum, dan dengan bantuan telunjuk menekan bagian LMA ke arah dinding faring posterior sampai penempatan dipastikan tepat, lalu balon LMA dikembangkan.…”
Section: Pendahuluanunclassified